The strategic management of maintenance - Hernández Carmona, Manuel (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
This work is framed in the area of Management and Engineering, proposing a pattern to Manage the Maintenance within a System Approach, evaluating the strategic position of the Organization of Maintenance to formulate strategics and so to guide the organization with respect to the implantation of the five basic activities that plan the postulates of Total Productive Maintenance (TPM).